Violations of The Cooperative Principle and Their Implications in The Context of The Animated Film Spongebob Squarepants: A Pragmatic Study - Thayyib, M. Asroruddin; Hermawan, Budi; Supriadi, Rinaldi (RETORIKA: Jurnal Ilmu Bahasa, 2025)
Both the speaker and the interlocutor are aware that there are rules governing their actions, language use, and interpretation of the actions and utterances of the interlocutor. Each participant in the speech act is responsible for their actions and deviations from linguistic rules in the linguistic interaction. The purpose of this study is to describe violations of the principles of conversational cooperation and implicature found in the Spongebob Squarepants animated film episode Cinta Tetangga. The research method used in this study is a qualitative descriptive research method. This study was conducted by observing and then analyzing excerpts from the main character's conversations that contain violations of cooperation and implicatures found in the film. The results of this study four maxims were violated: the maxim of quantity with 5 instances of violation, the maxim of quality with 2 instances of violation, the maxim of relevance with 6 instances of violation, and the maxim of manner with 2 instances of violation. In addition to cooperation violations, implications were found regarding the violation of the four maxims. The implicature of the maxim of quantity includes providing information, expressing objection, informing, requesting assistance, and advising. The implicature of quality includes knowing the data and feeling afraid. The implicature of relevance includes diverting the conversation, following the data, refusing to assist, and informing about the data. Finally, the implicature of the maxim of manner includes covering up ignorance and covering up something.